On inotropic effects of UTP in the human heart. Issue 8 (August 2019) - Neumann, J.; Hofmann, B.; Gergs, U.
Abstract: Uridine 5′-triphosphate (UTP) exerts a positive inotropic effect (PIE) in isolated electrically driven isolated right atrial trabeculae carneae from patients undergoing heart surgery. This review discusses some aspects of the current knowledge on the putative receptor(s) involved and the potential biochemical transduction steps leading to the PIE.